Studi komparasi traffic island Taman Titi Banda dengan traffic island Taman Dewa Ruci di Bali - Putra, Ida Bagus Eka Permana; Semarajaya, Cokorda Gede Alit; Pradnyawathi, Ni Luh Made (Jurnal Arsitektur Lansekap, 2021)
Traffic islands are parts of roads that cannot be passed by motorized vehicles, which include sidewalks, garbage dumps, plants, utilities, and signs. The traffic island park Titi Banda in Denpasar and the traffic island garden Dewa Ruci in Kuta have both the function of a traffic island and a landmark. Currently, the two traffic islands are getting additional functions, as a place for recreation and a place to turn around for vehicles.The purpose of this study are to inventory the existing conditions at both sites, compare the two traffic islands, and provide appropriate recommendations to maintain the main function of the two traffic islands. The method used in this research is a survey method, data collection method through observation, questionnaires and interviews.  The results showed that the traffic island design for the Titi Banda park and the traffic island for the Dewa Ruci park were not in accordance with the references or regulations regarding traffic islands and roads. The existing conditions on both sites are divided into hardscape elements and softscape elements. Comparisons are made on the two traffic islands in terms of pedestrians, entrance access, vegetation and road facilities by referring to regulations, and literature related to traffic island. The recommendations given include the addition of block tiles and warning tiles for pedestrians, entry access, replacement of vegetation, and providing road facilities that can provide a sense of security and comfort for pedestrians and road users. In addition, the recommendations given can maintain the main function of the site as a traffic island and landmark for the island of Bali and increase convenience for road users and pedestrians.